2007
DOI: 10.1016/j.ejpain.2006.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic activation and pain in response to low‐grade mental stress in fibromyalgia and shoulder/neck pain patients

Abstract: We found abnormal cardiovascular responses to a 60min long stressful task in fibromyalgia patients. Furthermore, we found a negative association between the heart rate response and the pain which developed during the stressful task in the fibromyalgia group, possibly a result of reduced stress-induced analgesia for fibromyalgia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 60 publications
(70 reference statements)
6
50
3
Order By: Relevance
“…chronic generalized pain syndromes, such as fibromyalgia (Nilsen et al, 2007) and irritable bowel syndrome (Bach et al, 2006), as well as in other illnesses, like posttraumatic stress disorder (Otis et al, 2003) and depression (Blackburn-Munro and Blackburn-Munro, 2001). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…chronic generalized pain syndromes, such as fibromyalgia (Nilsen et al, 2007) and irritable bowel syndrome (Bach et al, 2006), as well as in other illnesses, like posttraumatic stress disorder (Otis et al, 2003) and depression (Blackburn-Munro and Blackburn-Munro, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Stress exacerbates generalized pain syndromes such as fibromyalgia (Nilsen et al, 2007), irritable bowel syndrome (Bach et al, 2006), and interstitial cystitis (Temml et al, 2007), and painful inflammatory diseases like rheumatoid arthritis (Zautra et al, 2007). However, mechanisms mediating the impact of stress on pain are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Sympathetic hyperactivation has already been shown in fibromyalgia, [6] migraine, [7] and chronic neck and shoulder pain. [8] The sympathetic and parasympathetic systems work together to maintain the harmony of the human physiology, but this state can be disrupted by the chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…However, contradictory findings have also been reported. For example, altered cardiovascular responses to low-grade mental stress were found in fibromyalgia patients, whereas a group of subjects with neck-shoulder pain did not react significantly differently than healthy controls (Nilsen et al 2007). More recently, a study of individuals with trapezius myalgia showed an elevated heart rate at rest but no differences in stress responses compared with controls (Sjörs et al 2009).…”
Section: Autonomic Aberrations In Chronic Neck-shoulder Pain: Recent mentioning
confidence: 99%